Early treatment of schistosomal infection with artemether and praziquantel in rabbits. - Xiao Shu-hua; You Ji-qing; Mei Jin-yan; Jiao Pei-ying (Acta Pharmacologica Sinica; Vol 15, No 5 (September 1994): Acta Pharmacologica Sinica, 2016)
Artemether (Art, beta-methyl ether of artemisinin) first synthesized by Shanghai Institute of Materia Medica, Chinese Academy of Sciences, is effective against not only malaria but also schistosomiasis. When rabbits infected with Schistosoma japonicum cercariae for 7 d were treated ig with Art 10 mg.kg-1, the total worm reduction rates were 74.6-76.7%. If Art (10 mg.kg-1) was given once weekly after the first treatment for 3-4 times, the total worm reduction rate was > 98%, and most of the rabbits were free from female worms. When praziquantel (Pra) was given ig 40 mg.kg-1 to rabbits on d 21 after infection, and repeated once every week for 3 wk, most rabbits showed a total worm reduction rate > 98% with their livers showing normal or mild changes, and their parameters relevant to acute schistosomiasis were negative as compared to the controls. Hence Art and Pra are suggested to be used in field trial for control of acute schistosomiasis or reduction of the intensity of schistosomal infection.